American curiosity : cultures of natural history in the colonial British Atlantic world - Parrish, Susan Scott (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 2006)
Examines how various people in the British colonies understood and represented the natural world around them from the late sixteenth century through the eighteenth. The author uncovers early descriptions of American natural phenomena as well as clues to how people in the colonies construed their own identities through the natural world.